STYMULOWANIE ROZWOJU PRZEDSIĘBIORCZOŚCI W POLSCE - POSTULATY ROZWIĄZAŃ SYSTEMOWYCH - Jankiewicz, Sławomir (Wydział Prawa i Administracji UAM, 2003)
The development of small business in Poland began only after the change of the economic system. Small business in the initial stage o f the transformation successfully contributed to diminishing unemployment, and consequently lessened the negative effects of the liquidation and restructuring of state-owned companies, particularly in the areas that could not attract investment for their lack of appropriate infrastructure. After Poland joins the EU, small and medium-sized companies will also have a fundamental role in maintaining the high pace of economic growth. To fulfil that role, however, small and medium-sized business companies will need appropriate national policies. The ways of supporting small and medium-sized business have not been effective so far. The policies on this sector have been asynchronous if at all visible, while the measures have had only short-term effects. Consequently, the necessity arises to restructure the approach toward supporting small and medium-sized business so that the funds invested in that sector are not wasted. In the article an attempt has been made to formulate fundamental criteria that should constitute the basis for supporting small and medium-sized business.
STIMULATING BUSINESS DEVELOPMENT IN POLAND - POSTULATES FOR COMPREHENSIVE SOLUTIONS